Motor System Activation Predicts Goal Imitation in 7-Month-Old Infants. (May 2016) - Filippi, Courtney A.; Cannon, Erin N.; Fox, Nathan A.; Thorpe, Samuel G.; Ferrari, Pier F.; Woodward, Amanda L.
The current study harnessed the variability in infants' neural and behavioral responses as a novel method for evaluating the potential relations between motor system activation and social behavior. We used electroencephalography (EEG) to record neural activity as 7-month-old infants observed and responded to the actions of an experimenter. To determine whether motor system activation predicted subsequent imitation behavior, we assessed event-related desynchronization (ERD) at central sites during action observation as a function of subsequent behavior. Greater mu desynchronization over central sites was observed when infants subsequently reproduced the experimenter's goal than when they did not reproduce the goal and instead selected the nongoal object. We also found that mu desynchronization during action execution predicted the infants' later propensity to reproduce the experimenter's goal-directed behavior. These results provide the first evidence that motor system activation predicts the imitation of other individuals' goals during infancy.